Passive sensing data predicts stress in university students: a supervised machine learning method for digital phenotyping - Shvetcov, Artur; Funke Kupper, Joost; Zheng, Wu-Yi; Slade, Aimy; Han, Jin; Whitton, Alexis; Spoelma, Michael; Hoon, Leonard; Mouzakis, Kon; Vasa, Rajesh; Gupta, Sunil; Venkatesh, Svetha; et al. (Frontiers in Psychiatry, 2024)
Introduction University students are particularly susceptible to developing high levels of stress, which occur when environmental demands outweigh an individual’s ability to cope. The growing advent of mental health smartphone apps has led to a surge in use by university students seeking ways to help them cope with stress. Use of these apps has afforded researchers the unique ability to collect extensive amounts of passive sensing data including GPS and step detection. Despite this, little is known about the relationship between passive sensing data and stress. Further, there are no established methodologies or tools to predict stress from passive sensing data in this group. Methods In this study, we establish a clear machine learning-based methodological pipeline for processing passive sensing data and extracting features that may be relevant in the context of mental health. Results We then use this methodology to determine the relationship between passive sensing data and stress in university students. Discussion In doing so, we offer the first proof-of-principle data for the utility of our methodological pipeline and highlight that passive sensing data can indeed digitally phenotype stress in university students. Clinical trial registration Australia New Zealand Clinical Trials Registry (ANZCTR), identifier ACTRN12621001223820.